The Effect of Sign Implication in deriving the Psychological and Educational Meanings from Holy Qura’anic Texts - Mohammed, Marwa Qasim; Oudah, Sohaib Abbas (International Journal of Psychosocial Rehabilitation, 2020)
The Research aims at clarifying the intention of the approach of the holy Qura’an in education, direction and guidance. A lot of its words contained educational objective meanings and psychological treatments can’t be reached by merely looking to words and phrases but it is a must to direct the thought and deriving the essence of the text to know the implication of noble and fresh meanings. This can be done through sign implication only because it uncovers the essence of words needed. The significance of the reference path is to develop the hidden meanings and cannot be accessed by reading automatically. We should not depend on reference to devise legitimate meanings, but through comprehensive meanings. Such meanings could not identify their connotations only by giving applicable assiduous scientist. That the Qur’an educational curricula and psychological guidelines illustrated by the texts of Verbalism it brandished resignation does not permit. Addressed the Koran all community issues was a solution to every obstacle.